The Role of 3D Printed Spine Model in Complex Spinal Deformity Surgery; an Experience With a Case, Technical Notes and Review of the Literature - Hamed Hanif; Negin Safari; Reza Sharifi; Nima Ostadrahimi; Alaaeldin Ahmad (Clinical Case Reports)
ABSTRACT Complex spinal deformity in adults, often from neglected congenital deformities, poses surgical challenges. Understanding the 3D anatomy is crucial. A 3D‐printed spinal model aids pre‐operative planning, intra‐operative navigation, and education. It reduces surgery time, bleeding, and X‐ray dose, while improving screw placement accuracy and navigation of intra‐spinal pathologies.